Italy says no: the 2016 constitutional referendum and its consequences. Issue 2 (15th March 2017) - Pasquino, Gianfranco; Valbruzzi, Marco
Abstract: On 4 December 2016, Italians went to the polls to say yes or no in a popular referendum called by Prime Minister Matteo Renzi on his package of constitutional reforms. Turnout was very high: 65.5 per cent. The No vote scored an impressive victory: 59.1 per cent rejected those reforms; 40.9 per cent supported them. This article puts those reforms in the context of previous attempts to modify several articles of the Italian constitution. The authors analyze and criticize the substance of those reforms and explain their possible impact on the functioning of the Italian political system. The Yes and No alignments were somewhat diversified, while the Yes vote got a lot of support from an often curious combination of domestic and foreign bedfellows interested in the political stability of Renzi's government more than in any specific reform. Renzi's defeat led to his resignation. A new government was immediately formed. It is unclear when and whether other, different constitutional reforms will be formulated. The Italian political and institutional transition continues while once again attention is focused on the electoral law and on how to restructure the parties and the party system.